Desarrollo gametofítico de Metaxya rostrata (Filicales: Metaxyaceae) - Pérez- García, Blanca (Universidad de Costa Rica, 1994)
The morphogenic process of the gametophyte Metaxya rostrata is characterized by: a) germination of the Vittaria- type, b) development of a short initial filament, e) the early beginning of the laminar atage, and d) the early replacement of the initial meristematic by a pluricellular meristem, which corresponds to the Asdiantum-type development. The antheridia seem to be similar to those previously described as typical of the cyatheaceous ferns. After 270 days of cultivation, there were neither archegonia nor apogamous growth.